Modelling the Impact of Drug Abuse on a Nation’s Education Sector - Makinde, O. D.; Akanni, J. O.; Abidemi, A. (Journal of Applied Nonlinear Dynamics, 2026)
The problem of illicit drug use with its associated hazardous effects on social behaviour and human population dynamics require an intervention. In this study, a compartmental deterministic model for the dynamics of illicit drug use student population is proposed and analysed. The illicit drug use threshold, R_0, associated with the model is computed. The Centre Manifold Theorem is used to establish bifurcation phenomenon. By constructing suitable Lyapunov functions, the global asymptotic stability of the illicit drug-free and illicit drug-present equilibria exhibits by the model is established. It is shown that the illicit drug-free equilibrium is globally asymptotically stable if R_0